Evaluating the Framework of the Notion Entrepreneurial Intention and Resilience: A Prisma Approach - Ayesha Yaseen; Raflis Bin Che Omar; Lokhman Hakim Osman; Roshayati Binti Abdul Hamid (Administrative Sciences, 2025)
This study reviews various academic discussions utilising distinct interpretations of entrepreneurship and resilience. The inadequacies of contemporary literature are explored and avenues for subsequent studies are offered in light of these discussions. Notable shifts in literature across themes, eras, and contexts have been documented. The body of literature has been steadily expanding over time, with a significant portion of research included in this SLR published from 2010 to 2024, which was not considered in earlier SLRs. A methodical, multidisciplinary evaluation of 44 publications divided into multiple academic dialogues was conducted to lay the groundwork for critical examination of each field of study. Resilience in the modern era encompasses not only the power to bounce back from stressful situations and adjust to a changed environment but also the dynamic process to improve learning capacity and foster personal development through continuous self-improvement, the acquisition of novel experiences and a forward-leaping framework. These findings contribute to the clarification and critical analysis of the current state of entrepreneurial resilience which will have several policies implications.